SISTEM INFORMASI GEOGRAFIS LAPANGAN PERTANDINGAN PORA KE XIV TAHUN 2022 DI KABUPATEN PIDIE BERBASIS QGIS - Annida Adillah; Yuswardi; Cut Lilis Setiawati (Sagita Academia Journal, 2024)
Pidie Regency is an area that provides many field facilities to implement. After conducting research directly by the authors, the authors found more than 30 fields to serve as PORA venues in Pidie District. However, not everyone knows the location of the field, including match information. This writing will discuss the creation of geographic information system (GIS) locations for Pidie Regency, especially the places or points where PORA XIV fields in Pidie Regency are increasing. The method used in this research is a geographic-based system or Global Information System (GIS). The aim of this research is how this system can display data from the field site in the form of maps or spatial data so that it can be more easily understood by users. Implementation of this system is made using the programming language used is PHP, HTML and CSS. Meanwhile, for processing the database, it uses the Mariadb database, which is a database capable of processing spatial data and attribute data. The result of this distribution analysis is a map of the playing fields in Pidie Regency.